A New Approach for Root Surface Biomodification Using Injectable Platelet-Rich Fibrin (I-PRF) - İzol, Bozan Serhat (Med Sci Monit, 2019)
BACKGROUND: This study investigated the potential effects of Injectable Platelet-Rich Fibrin (I-PRF) on root coverage of free gingival graft surgery. MATERIAL/METHOD: A total of 40 patients with Miller class I or II gingival recession were included. The patients who participated in this study were randomly divided into 2 groups, including the control and experiment groups. The patients in the control group were treated only with free gingival graft (FGG). The patients in the experiment group were treated with free gingival graft and injected with I-PRF as a root surface biomodification agent (FGG+I-PRF). The patients were called back after 3 months, and the amount of exposed root surface was determined and compared to the preoperative findings. RESULTS: The mean initial exposed root surface was 4.7±1.49 mm for the FGG+I-PRF group, 4.1±1.07 mm for the FGG group, and 4.4±1.31 mm for all subjects. Three months after the operation, the mean root surface coverage values of the 2 groups were 3.5±1.05 and 3.9±0.78 mm in the control and experiment groups, respectively. CONCLUSIONS: The findings showed that the injection of Injectable Platelet-Rich Fibrin (I-PRF) had a positive effect on root coverage in free gingival graft surgery.